Socio - Psychological Problems of Pedagogical Activity - Shoyimova Shokhista Sanakulovna (Researchparks Publishing, 2023)
Pedagogical activity is a complex process, which manifests various social and psychological aspects. Pedagogical activity was scientifically analyzed in the article, and models of pedagogical activity were studied based on the principles of a systematic approach. Also, the opinions of foreign scientists on the content and structure of pedagogical activity are given. Five structural components of the application of general systems theory in the analysis of pedagogical activity are distinguished.